E-Government Maturity Model Based on SPBE at Department of Spatial Planning and Development - Endang Amalia; Dani Hamdani; Ucu Nugraha (International Journal of Engineering Continuity, 2024)
Sistem Pemerintahan Berbasis Elektronik known as SPBE is a government administration that utilizes information and communication technology to provide services with the aim of realizing clean, effective, transparent, and accountable government governance, quality, and trustworthy public services. Because he role of ICT in supporting work processes and services in achieving the vision and mission of the Regional Government of West Java Province is very important, it is necessary to evaluate the use and implementation of ICT solutions for continuous improvement in all Regional Apparatus. In the department spatial planning and development, e-government maturity measurements are carried out in 4 domains (application, infrastructure, information security and IT governance and) by adopting a descriptive research method using questionnaire data with a scale of 5 likers. The results showed the evaluation of the maturity of the SPBE in department spatial planning and development obtained a “Very Poor” category with a total index value of 0.61. This research also provides recommendations and considerations in making decisions on how to take policies in implementing e-Government Implementation in the community development service to determine the development priority scale from the level of maturity.